2001
DOI: 10.1111/0026-7902.00117
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Knowledge of Icraab, Lexical Knowledge, and Reading Comprehension of Nonnative Readers of Arabic

Abstract: This article reports on an investigation into the role played by knowledge of both icraab and vocabulary in the reading comprehension of American learners of Arabic as a foreign language (AFL). Two groups (46 participants), proficient and less proficient, of nonnative readers of Arabic read an expository text, wrote an immediate recall protocol in their first language to measure their overall reading comprehension, and completed a vocabulary task and an icraab task. Whereas the analysis of the data revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 44 publications
1
13
0
1
Order By: Relevance
“…Our results also underscore the important role vocabulary and grammar knowledge play in determining listening comprehension scores. Similar to L2 reading studies which report strong links between vocabulary knowledge and comprehension (Hawas, 1990;Khaldieh, 2001;Koda, 1992;Pulido & Hambrick, 2008;Shiotsu, 2010), strong associations were found between vocabulary knowledge and L2 listening comprehension (Matthews & Cheng, 2015;Sağlam, 2014;Staehr, 2009;Teng, 2014Teng, , 2016. It is strongly advocated that core word knowledge should be promoted to enable learners to comprehend texts (Koda, 2005).…”
Section: Figure 12 Reported Correlations Between Anxiety and Listenisupporting
confidence: 64%
“…Our results also underscore the important role vocabulary and grammar knowledge play in determining listening comprehension scores. Similar to L2 reading studies which report strong links between vocabulary knowledge and comprehension (Hawas, 1990;Khaldieh, 2001;Koda, 1992;Pulido & Hambrick, 2008;Shiotsu, 2010), strong associations were found between vocabulary knowledge and L2 listening comprehension (Matthews & Cheng, 2015;Sağlam, 2014;Staehr, 2009;Teng, 2014Teng, , 2016. It is strongly advocated that core word knowledge should be promoted to enable learners to comprehend texts (Koda, 2005).…”
Section: Figure 12 Reported Correlations Between Anxiety and Listenisupporting
confidence: 64%
“…Abu-Rabia & Sanitsky (2010) 0.184 -0.135 0.469 1.132 0.258 Khaldieh (2001) 0.276 -0.016 0.524 1.858 0.063 Haynes & Carr (1990) 0.371 0.129 0.571 2.941 0.003 August (2006) 0.399 0.150 0.601 3.046 0.002 Guo & Roehrig (2011) 0.580 0.496 0.653 10.986 0.000 Shiotsu (2010) 0.624 0.536 0.699 10.751 0.000 Nassaji & Geva (1999) 0.660 0.488 0.783 5.986 0.000 Choi et al (2003): Sample 1 0.714 0.619 0.789 10.169 0.000 Irvine et al (1974) 0.736 0.655 0.800 11.762 0.000 Lefrancois & Armand (2003) 0.791 0.631 0.887 6.354 0.000 Van Gelderen et al (2004) 0.800 0.754 0.839 18.318 0.000 Bensoussan & Ramraz (1984) 0.827 0.795 0.855 24.496 0.000 Henning et al (1981) 0.830 0.779 0.870 15.985 0.000 Choi et al (2003): Sample 2 0.961 0.945 0.972 21.724 0.000 Sang et al (1986) 0.990 0.989 0.991 120.706 0.000 Shiotsu & Weir (2007)…”
Section: Lower Upper Correlation Limit Limit Z-value P-valuementioning
confidence: 99%
“…In the Arabic L2 context, few studies were conducted on the role of Arabic script and diacritics. One such study was conducted by Khaldieh (2001) who investigated the role of knowledge of ʔiʕrāb 'case and mood' endings (i.e., inflectional endings involving vowels in final word position) 3 and vocabulary on reading comprehension among American learners of Arabic as an L2. The study employed an expository text, vocabulary, and ʔiʕrāb tasks, and an immediate recall protocol conducted in the learners' native language.…”
Section: Arabic L2 Research On Diacriticsmentioning
confidence: 99%
“…The findings revealed that participants relied on knowledge of vocabulary more than that of ʔiʕrāb. Khaldieh (2001) suggested further research, using texts employing classical Arabic prose, may provide evidence for the importance of ʔiʕrāb endings in reading comprehension according to text type.…”
Section: Arabic L2 Research On Diacriticsmentioning
confidence: 99%